Pengembangan Aplikasi Youniverse Berbasis Mobile untuk Mendukung Kegiatan Event Komunitas - Chaulina Alfianti Oktavia; Meivi Kartikasari; Ersandi Mukhibillah (Ikatan Ahli Informatika Indonesia, 2024)
This research develops the Youniverse mobile application to support community event activities, specifically for the Mobile Class Community of Malang. The application aims to address various issues in event management that are still conducted manually, such as registration difficulties, delays in information dissemination, and data security risks. The research methods include problem identification, problem analysis, data collection through observation, interviews, and questionnaires, as well as literature studies and competitor analysis. The Youniverse application is designed using Dart and Flutter technology for multiplatform compatibility, and Firebase for a secure and scalable backend. The main features of the application include online event registration, real-time notifications, QR code-based check-in, event calendar, ticket management, and feedback collection. The application implementation is carried out with thorough testing to ensure all functions run smoothly. The research results indicate that the Youniverse application successfully improves efficiency, security, and user experience in community event management. This research provides practical contributions to the development of technology to support community activities and offers suggestions for further research in various fields beyond informatics.